Bentuk Perlindungan Bagi Perempuan yang Dipekerjakan Sebagai Pekerja Seks Komersil (PSK) - Debby Pratiwi Surbakti; Suriani Siagian; Emmi Rahmiwita Nasution (Universitas Muhammadiyah Sumatera Utara, 2020)
The high number of unemployed people in Indonesia has made people ignore the ban from the state not to commit a crime. Including trafficking in people. The target of victims in this crime are usually women. Women who are victims are mostly employed as Commercial Sex Workers (CSWs). The modus operandi is used by various actors to run their business. Usually by luring work outside the city. The formulation of the problem to be discussed is regarding a general review of Commercial Sex Workers (CSWs) and forms of legal protection for women employed as Commercial Sex Workers (CSWs). The research method is normative with legal materials derived from laws and regulations, books or other scientific works as well as dictionaries that explain the problem. Procedure for collecting legal material by searching the Asahan University Faculty of Law library to find legal books and legislation relating to forms of protection for women employed as Commercial Sex Workers (CSWs) by analyzing existing legal materials and then later from the management of these legal materials conclusions drawn by the authors. Regulations regarding the crime of trafficking in persons are regulated through Law Number 21 of 2007 concerning Eradication of the Criminal Act of Trafficking in Persons. Which includes the scope of trafficking in persons, sanctions, and legal protection, and so forth. So that conclusions can be drawn from the writing of this study is the regulation and legal protection regarding these criminal acts are clearly regulated in the Act. Thus, the author's advice law enforcement officials can enforce the law in accordance with statutory regulations.